Characterization of a Trametes versicolor aflatoxin B1-degrading enzyme (TV-AFB1D) and its application in the AFB1 degradation of contaminated rice in situ - Yang, Peizhou; Xiao, Wei; Lu, Shuhua; Jiang, Shuying; Jiang, Suwei; Chen, Jianchao; Wu, Wenjing; Zheng, Zhi; Jiang, Shaotong (Frontiers in Microbiology, 2022)
Aflatoxin B1 (AFB1) contaminates rice during harvest or storage and causes a considerable risk to human and animal health. In this study, Trametes versicolor AFB1–degrading enzyme (TV–AFB1D) gene recombinantly expressed in engineered E. coli BL21(DE3) and Saccharomyces cerevisiae. The TV–AFB1D enzymatic characteristics and AFB1 degradation efficiency in contaminated rice were investigated. Results showed the size of recombinant TV-AFB1D expressing in E. coli BL21(DE3) and S. cerevisiae was appropriately 77 KDa. The kinetic equation of TV-AFB1D was y=0.01671x+1.80756 (R2=0.994, Km=9.24 mM, and Vmax=553.23 mM/min). The Kcat and Kcat/Km values of TV-AFB1D were 0.07392 (s−1) and 8 M−1 s−1, respectively. The AFB1 concentration of contaminated rice decreased from 100 μg/mL to 32.6 μg/mL after treatment at 32 °C for 5 h under the catabolism of TV-AFB1D. S. cerevisiae engineered strains carrying aldehyde oxidase 1 (AOX1) and Cauliflower mosaic virus 35 S (CaMV 35 S) promoters caused the residual AFB1 contents respectively decreased to 3.4 and 2.9 μg/g from the initial AFB1 content of 7.4 μg/g after 24 h of fermentation using AFB1-contaminated rice as substrate. The AFB1 degradation rates of S. cerevisiae engineered strains carrying AOX1 and CaMV promoters were 54% and 61%, respectively. Engineered S. cerevisiae strains integrated with TV-AFB1D expression cassettes were developed to simultaneously degrade AFB1 and produce ethanol using AFB1-contaminated rice as substrate. Thus, TV-AFB1D has significant application potential in the AFB1 decomposition from contaminated agricultural products.